2003
DOI: 10.1542/peds.112.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Antecedent Risk Factors of Early and Late Periventricular/Intraventricular Hemorrhage in Premature Infants

Abstract: Early and late P/IVH have distinct and different risk factors. Early P/IVH is associated with vaginal delivery and possibly low Apgar scores. Late P/IVH is associated with antecedent low SVC flow in the first day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
202
1
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(228 citation statements)
references
References 35 publications
15
202
1
10
Order By: Relevance
“…26 The association between vaginal delivery and IVH is controversial. [26][27][28][29][30] In this case-control study, we found that vaginal delivery was a risk factor for severe IVH. Low superior vena cava flow, resulting from the inability of the immature heart to withstand high systemic resistance after birth, is associated with an increased risk of late IVH.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…26 The association between vaginal delivery and IVH is controversial. [26][27][28][29][30] In this case-control study, we found that vaginal delivery was a risk factor for severe IVH. Low superior vena cava flow, resulting from the inability of the immature heart to withstand high systemic resistance after birth, is associated with an increased risk of late IVH.…”
Section: Discussionmentioning
confidence: 68%
“…Low superior vena cava flow, resulting from the inability of the immature heart to withstand high systemic resistance after birth, is associated with an increased risk of late IVH. 30,31 As the majority of hemorrhages develop after the improvement of the superior vena cava flow, hypoperfusion-reperfusion injury was assumed to be the cause of late IVH. In contrast, normal superior vena cava flow was observed among babies with early IVH; hence, it is believed that the hypoperfusion-reperfusion cycle occurred earlier.…”
Section: Discussionmentioning
confidence: 99%
“…At the time the autoregulation studies were conducted, 11 infants were being administered cardiovascular medications due to circulatory impairment and 27 were placed on invasive mechanical ventilation. The serial echocardiography assessment showed that 9 of the 54 infants had SVC flow below the cut-off value of 41 ml/kg per min (defined as low SVC flow) (7)(8)(9) at some point during the study. During the observation period, the SVC flow measurement closest to a given epoch was recorded.…”
Section: Mechanistic Approach In Autoregulationmentioning
confidence: 99%
“…7 In some babies, SVC flow dropped to extremely low levels during this nadir, and these babies were particularly at a high risk of a range of adverse outcomes including, intraventricular hemorrhage (which seems to occur as SBF improves), death, necrotizing enterocolitis and a poor 3-year neurodevelopmental outcome. 4,[7][8][9] Data are now emerging from other groups that are duplicating some of these findings. 10 Most importantly, there is a very weak relationship between these measures of SBF and BP (Figure 3).…”
Section: Studies Of the Systemic Circulationmentioning
confidence: 99%